The Characteristics of Synthetic Chitosan Prepared from Snail Shells of Achatina Fulica - Jacob A. Frans; Suwari; Luther Kadang (Journal of Applied Chemical Science, 2013)
A synthetic chitosan prepared from snail shells of achatina fulica has been done. The chitosan was yielded by the isolation stages that involved deproteinization, demineralization, and deacetylation that was by NaOH 3.5%, HCl 1 M, and 50% NaOH, respectively, and followed by determination of moisture content, ash content, viscosity, degree of deacetylation and functional groups. The moisture and ash contents were determined by a gravimetric method, the viscosity was by Ostwald instrument, while the degree of deacetylation and the functional groups were by FT-IR. The results showed that using those protocols provided 23.20% of chitosan content from the original snail shell material. The chitosan yielded had (in %) moisture and ash contents, viscosity, and degree of deacetylation were 0.24, 20.0, 198.3, and 68.5%, respectively. The functional group detected that involved –OH group was appeared at 3433.06 cm-1, while the -CH2- asymmetry and -CH2- symmetry were appeared at 2923.88 cm-1 and 2875.67 cm-1, respectively. The functional groups of -CH3-, C=O amide, and C-N aliphatic amines were appeared at 2979 cm-1, 1789.82 cm-1, and 1494.73 cm-1, respectively. The twin band of -NH2 was not found because of overlapping occurred between the -OH and-NH amine groups.